2018
DOI: 10.1111/1750-3841.14079
|View full text |Cite
|
Sign up to set email alerts
|

Growth Capacity of a Novel Potential Probiotic Lactobacillus paracasei K5 Strain Incorporated in Industrial White Brined Cheese as an Adjunct Culture

Abstract: The launch on market of novel foods developed by the incorporation of functional ingredients provides potential benefits to consumers' diet and new business opportunities for producers. Probiotic food products are one significant category of functional foods. Thus, this study focused on the development of a novel ready-to-use freeze-dried potential probiotic biocatalyst for functional white brined cheese production. The potential industrial application of such biocatalysts is highlighted by their incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
5
31
0
Order By: Relevance
“…After the 1st week of cold storage, the viability of IC was statistically higher compared to the viability of FC. This may be credited to the protective effect of the prebiotic immobilisation substrate, as other researchers have demonstrated the employment of DWB as a carrier of lactic acid bacteria for fermented dairy products production [ 31 , 39 ]. Furthermore, there are reports in the literature claiming that immobilization clearly protects cells from the acidic environment of the juices and leads to a limited viability loss [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the 1st week of cold storage, the viability of IC was statistically higher compared to the viability of FC. This may be credited to the protective effect of the prebiotic immobilisation substrate, as other researchers have demonstrated the employment of DWB as a carrier of lactic acid bacteria for fermented dairy products production [ 31 , 39 ]. Furthermore, there are reports in the literature claiming that immobilization clearly protects cells from the acidic environment of the juices and leads to a limited viability loss [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…At day 60, the composition of cheeses was found within the range of other Italian ewes' milk cheeses (Coda et al, 2006). It has been previously observed that the addition of probiotic microorganisms did not affect the main compositional parameters (moisture, salt, fat and protein contents) of different cheese types (Zhang et al, 2013;Perotti et al, 2014;Terpou et al, 2018), and did not negatively influence the ripening process of Edam cheese (Sabikhi et al, 2014).…”
Section: Physico-chemical Composition Of Caciotta Cheese During Ripeningmentioning
confidence: 52%
“…It has been demonstrated that efficient starter culture and/or an enforcement by an adjunct is essential to achieve a fast pH decrease, thus contributing to control these undesired microorganisms (Terpou et al, 2018). The viable counts of LAB and yeasts are shown in Table 3.…”
Section: Microbiota Analysismentioning
confidence: 99%
“…The aroma compounds were extracted by headspace solid‐phase microextraction (HS‐SPME) (Nzekoue et al., 2019; Reyes‐Díaz et al., 2019; Terpou et al., 2018). Prior to extraction, the milk cake samples were thawed at room temperature for 4 hr and then cut into small squares of uniform size.…”
Section: Methodsmentioning
confidence: 99%